Addressing xenophobia in South Africa : drivers, responses and lessons from the Durban untold stories - Ngcamu, Bethuel Sibongiseni; Mantzaris, Evangelos (Emerald Publishing Limited, 2021)
Xenophobia is a salient issue in South Africa. Prominent episodes of violence targeting migrants and refugees have received enormous attention from scholars, researchers, policymakers, government officials, and media agencies. Focusing on a prominent episode of anti-immigrant violence in the Durban area of the KwaZulu-Natal province, Addressing Xenophobia in South Africa identifies the hidden, less addressed dimensions and catalysts of this violence. Bethuel Sibongiseni Ngcamu and Evangelos Mantzaris have carried out a cutting-edge investigation of the multiple set of factors that generate public violence. By examining particular social dynamics and circumstances in marginal locations, and drawing on interviews with key informants, this book also provides a critique of the response of the South African government. Covering the role of economic competition, the media, and the nuances of micro-politics and localised processes that fuel violent xenophobia in townships and other settlements, this book provides a uniquely detailed study of an episode of large-scale violence involving migrants and refugees. Showcasing information not captured by other research methods, the in-depth local-level research with multiple actors and stakeholders, this book yields new and interesting information, left previously undiscovered, about important social and political processes at a local level.